Practice Of Fertilizer Debt With a Profit Sharing Return System In Badan Usaha Milik Desa (BUMDes) Sharia Economic Law Perspective - Dwi Atya Illahi (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Badan Usaha Milik Desa (BUMDes) are village business institutions established with the aim of strengthening the vilslage economy which is managed by the community and village government and is formed based on the needs and potential of the village. There are various types of businesses that are run. One of them is HIPPA which involves several contracts. In terms of Sharia Economic Law, the use of the chosen contract must be in accordance with its implementation. If there is a merger of contracts, the law of origin of the contracts must be clear. This research uses an empirical research type, using a qualitative approach with logic and theoretical truth as well as a sociological and anthropological approach when conducting a survey for the collection of legal materials. The results of this study are 1) BUMDes in Kenongo village implements a debt and credit system with a return for profit sharing by dividing the harvest that has been obtained by farmers. 2) Repayment of fertilizer debt in addition to using the qardh contract, there is another contract, namely the mudhorobah contract so that both of them will relate to the application of multi contract in accordance with sharia economic law or not.